Oñati Proceedings: Disputes and litigation - García Ramos, José Ignacio (dir.) (1991)
Contiene: Legal cultures compared; Civil litigation in Belgium; Civil litigation in WÜrttemberg, Germany, from 1821 to 1915; Japanese claim consciousness; A tentative list of the japenese participants in the Amsterdam Symposium on Comparative Legal Cultures and the titles of their papers; Judicial order, social order, political order; Choosing between paternalism and legalism in juvenile justice; French cabinet justice and family autonomy; Contentieux familial et médiation.